2004
DOI: 10.1159/000075064
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Intestinal Histology in Neonates with Congenital Anomalies of the Gastrointestinal Tract

Abstract: In animal models, when swallowing is experimentally prevented in utero, bowel length and weight are reduced, and villus height, crypt depth, and villus function are retarded. Little is known about the intestinal histology in infants with gastrointestinal (GI) tract anomalies. We examined the histological architecture of the intestine in neonates with GI anomalies in comparison to that of normal fetuses. Villus height, area, and length and crypt depth of normal fetuses were quantified in the proximal small bowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Using a fetal sheep model, Trahair and Harding (36) showed that experimental obstruction of the fetal esophagus or the small intestine caused ultrastructural abnormalities in IECs such as delayed disappearance of the apical endocytic network, disrupted or absent microvilli, glycogen accumulation, and inappropriate cell extrusion. Similarly, we have previously shown that human neonates with congenital intestinal obstruction have histopathological abnormalities such as villus blunting and loss of crypt depth with abnormal crypt organization (10). In undifferentiated 15-day murine fetal duodenal explants, rat amniotic fluid extracts have been shown to induce IEC proliferation and promote crypt and villus formation (23).…”
Section: Discussionmentioning
confidence: 85%
“…Using a fetal sheep model, Trahair and Harding (36) showed that experimental obstruction of the fetal esophagus or the small intestine caused ultrastructural abnormalities in IECs such as delayed disappearance of the apical endocytic network, disrupted or absent microvilli, glycogen accumulation, and inappropriate cell extrusion. Similarly, we have previously shown that human neonates with congenital intestinal obstruction have histopathological abnormalities such as villus blunting and loss of crypt depth with abnormal crypt organization (10). In undifferentiated 15-day murine fetal duodenal explants, rat amniotic fluid extracts have been shown to induce IEC proliferation and promote crypt and villus formation (23).…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with these findings, human neonates with congenital intestinal obstruction also show villus blunting and shallow, poorly organized crypts distal to the site of obstruction. 13 In Trahair’s model, the mucosal defects were gradually reversed following the removal of esophageal ligatures and restitution of AF ingestion but not by the infusion of Ringer’s lactate, indicating that the “trophic” effects of AF were secondary to the bioactive molecules present in AF and not merely due to the flow of fluid through the gut lumen. 14 …”
Section: Cytokines In the Developing Intestinementioning
confidence: 99%
“…[15][16][17] Experiments of Karnak 16 and Trahair 17 showed that the beneficial effect of swallowed amniotic fluid on bowel development comes from the enterocyte growth factors within the fluid, not from the liquid itself. The enterocyte growth factors present in amniotic fluid are also present in colostrum and human milk.…”
Section: Discussionmentioning
confidence: 99%